Discourse semiotics of gender in two novels "This street has no speed bumps "and "Rahesh". - نرجس ghabeli; alireza asadi; ali soltani (زن در فرهنگ و هنر)
Novels, As cultural products, represent a society with various discourses. Each discourse, with its own configurations, is constantly trying to make its meanings hegemonic. The current research is an attempt to analyze the discourse semiotics of gender with an emphasis on the theory of Laclau and Mufehe in the two novels "This street has no speed bumps" and "Rahesh". The main issue in the current research is how "gender" is represented in these novels. Also, how gender thoughts are reflected through the author's mentality in writing the novel and what is the author's point of view towards them. In terms of methodology, it is a descriptive and qualitative research, which uses library method to collect data. According to this method, the analysis of the novel includes three levels: textual analysis, intertextual analysis, contextual analysis. Textual analysis is dedicated to the semiotics of the novel's characters and finding the discourse order of the novel; In intertextual analysis, each novel is compared with novels of the same period; in contextual analysis, the relationship between the novel and larger social space is examined. Finally, the analysis of the propositions revealed that the main concern and theme of the novels; The obvious conflict between tradition and modernity lies in the social construction of gender, which is implicitly included in the inner layers of the text and lexical reflection, and the main character of the novels at all stages are in the conflict between the biological construction of gender and its social construction.